Growth mechanisms of Ca- and P-rich MAO films in Ti-15Zr-xMo alloys for osseointegrative implants - Correa, D. R.N. (2018)
In this study, a micro-arc oxidation treatment was applied to Ti-15Zr-xMo (x = 0, 5, 10 and 15 wt%) alloys to produce porous oxide layers enriched with bioactive ions (calcium and phosphorus) for use as osseointegrative implants. Biocompatibility studies, namely metabolic activity, mineralization and differentiation studies were conducted with human osteoblastic cell line SAOS-2. A typical porous coating was obtained in all samples, with similar morphologies and thicknesses, which were found to be dependent on the maximum applied voltage. Calcium and phosphorus ions were incorporated into the films, as indicated by EDX analysis. Chemical analyses indicated that the films were composed preferentially of Ti and Zr oxides. XRD patterns revealed mostly substrate Ti phases. However, cross-sectional TEM imaging and automated phase and orientation mapping showed distinct amorphous and nanocrystalline regions within the films, with a higher fraction of Ca atoms incorporated in the outer layer. After immersion in Hanks’ Balanced Salt Solution (HBSS) for seven days, small amounts of calcium phosphate precipitates were observed at the surface of all samples which were confirmed by ICP-AES measurements, indicating that the MAO treatment possibly introduced a considerable bioactive response in the samples. Biological results indicate that Ti-15Zr-15Mo MAO-treated surfaces are biocompatible and induce a higher osteoblasts viability and mineralization. The combination of porous structure and bioactive composition of the oxide layers can be suitable for use as advanced biomedical implants with osseointegration ability.